Molecular Mechanisms Linking Exercise to Cancer Prevention and Treatment - Hojman, Pernille; Gehl, Julie; Christensen, Jesper F.; Pedersen, Bente K. (Cell metabolism, 2018)
The benefits of exercise training for cancer patients are becoming increasingly evident. Physical exercise has been shown to reduce cancer incidence and inhibit tumor growth. Here we provide the status of the current molecular understanding of the effect of exercise on cancer. We propose that exercise has a role in controlling cancer progression through a direct effect on tumor-intrinsic factors, interplay with whole-body exercise effects, alleviation of cancer-related adverse events, and improvement of anti-cancer treatment efficacy. These findings have wide-ranging societal implications, as this understanding may lead to changes in cancer treatment strategies. Hojman et al. discuss the role of exercise in controlling cancer progression through direct effects on tumor-intrinsic factors, interplay with whole-body exercise effects, alleviation of cancer-related adverse events, and improvement of cancer treatment efficacy. Understanding these mechanistic interactions is warranted for pursuing exercise as cancer medicine.